Residential Electricity Consumption Patterns and their Relationship to Commute Times by Mode - Juan Acosta-Sequeda; Hevar Palani; Ali Movahedi; Aslihan Karatas; Sybil Derrible (Findings, 2023)
In this study, the correlation between emerging electricity consumption patterns in the Chicago area and commute times to work by mode are explored. We found that when aggregating similar daily electricity consumption curves, areas sharing similar electricity patterns are geographically closer to each other and located in regions that are strictly urban or suburban. Furthermore, we modelled these clusters in terms of commute times to work by mode. The findings suggest that morning electricity consumption differs significantly among clusters and that it is caused primarily by long duration public transport trips.